Synthetic aperture radar compact polarimetry for sea ice surveillance - Espeseth, Martine Mostervik (UiT The Arctic University of Norway, 2015)
The focus of this thesis is to investigate the use of synthetic aperture radar (SAR) compact polarimetry for studies of sea ice. Data obtained from quad-polarimetric SAR systems have already been studied extensively for sea ice monitoring. This thesis focuses on finding parallels to quad-polarimetric features from the compact-polarimetric data. This is achieved through the reconstruction of a pseudo quad-polarimetric sample covariance matrix. The main contribution of this thesis is the suggestion of new reconstruction techniques for sea ice covered SAR scenes. Most of the estimated polarimetric features relevant to sea ice monitoring are successfully reconstructed. Furthermore, a comparison between the different reconstruction techniques is presented for different sea ice types. It is shown that the cross-polarization intensity can be reconstructed for different sea ice types, but that the performance is strongly affected by the choice of reconstruction method. The proposed modified Souyris' reconstruction technique turns out to be the best method for achieving high performance for different polarimetric features representing different sea ice types. Additionally, three other methods are suggested, namely a model-based, an eigenvalue-based, and a DoP-based reconstruction method. Each of these methods produce a higher accuracy than the existing reconstruction methods for most of the polarimetric features. Remote sensing instruments have been extensively used as a tool for sea ice monitoring. Information about sea ice is important for multiple industries like oil and gas, fishing, research communities, and tourism. Full- and dual polarimetric SAR instruments have been used to extract useful information about the sea ice surface, but now a new polarimetric mode has been invented. In its infancy, the theoretical foundation of compact polarimetry was presented by Souyris, Nord, and later Raney with the hybrid-pol mode. However, compact polarimetry—especially the hybrid-pol mode—has proved valuable, and has in later ...